Extending the Shared Socioeconomic Pathways (SSPs) to support local adaptation planning—A climate service for Flensburg, Germany. (March 2021) - Reimann, Lena; Vollstedt, Bente; Koerth, Jana; Tsakiris, Maureen; Beer, Martin; Vafeidis, Athanasios T.
Highlights: We develop local Shared Socioeconomic Pathways (SSPs) as a climate service. We present and discuss a multi-scale co-production approach employed for extending the SSPs. We engage local stakeholders in an iterative manner based on a Living Lab approach. The extended local SSPs are embedded in and coherent with the global-scale SSPs. Abstract: In this study, we extend the global-scale Shared Socioeconomic Pathways (SSPs) to develop local SSPs as a tool to inform adaptation decisions (a so-called 'climate service') for the city of Flensburg, Germany. Flensburg experiences regular coastal flooding during storm events, which is expected to increase with sea-level rise (SLR). To develop robust adaptation strategies under the uncertainties of future SLR and socioeconomic development in the city, local socioeconomic scenarios can help explore plausible future socioeconomic conditions and how these conditions drive adaptation strategies. We employ a multi-scale co-production approach for developing such local scenarios. Using the global SSPs as boundary conditions, we construct local SSP narratives based on local SSP elements that we compile during the process. We integrate local stakeholder knowledge into the local SSPs in an iterative manner with the help of focus group discussions, a scenario workshop, and email feedback. This process results in four local SSP narratives that explore alternative trends in socioeconomic development in Flensburg and are embedded in developments at national to global scales. Due to their local relevance, the extended local SSPs can serve as a climate service to support Flensburg in developing adaptation plans to cope with the future impacts of SLR.